2022
DOI: 10.1016/j.lana.2022.100197
|View full text |Cite
|
Sign up to set email alerts
|

A temporal study of Brazilian pregnant and postpartum women vulnerability for COVID-19: Characteristics, risk factors and outcomes

Abstract: Background During the COVID-19 second wave in Brazil, there has been a significant increase in the number of daily cases and deaths, including pregnant and postpartum women. We assess risk factors and outcomes for this priority group compared to the COVID-19 non-pregnant cohort in two epidemic waves. Methods In this retrospective cohort study we evaluated data of hospitalized pregnant, postpartum, and nonpregnant women aged 15-44 years, between epidemiological weeks 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“… [25] , [50] In addition, pregnant people were admitted to the ICU, mechanical ventilation, and died at higher rates during the second wave of COVID-19 (variant not specified) in Brazil. [52] Overall, there are relatively few large population cohort studies that examine the effects of different variants on maternal-fetal outcomes. Given the diversity of clinical outcomes between variants it may be important in future studies to consider the variant of infection a feature when examining and understanding relative risk of maternal-fetal outcomes following a maternal COIVD-19 infection.…”
Section: Maternal Sars-cov-2 Infection Impact On Maternal-fetal Outcomesmentioning
confidence: 99%
“… [25] , [50] In addition, pregnant people were admitted to the ICU, mechanical ventilation, and died at higher rates during the second wave of COVID-19 (variant not specified) in Brazil. [52] Overall, there are relatively few large population cohort studies that examine the effects of different variants on maternal-fetal outcomes. Given the diversity of clinical outcomes between variants it may be important in future studies to consider the variant of infection a feature when examining and understanding relative risk of maternal-fetal outcomes following a maternal COIVD-19 infection.…”
Section: Maternal Sars-cov-2 Infection Impact On Maternal-fetal Outcomesmentioning
confidence: 99%
“…The data in the Malawian study was collected from 33 district and central hospitals throughout Malawi 2 . Nationwide data were collected from the Influenza Epidemiological Surveillance Information System (SIVEP‐Gripe) in Brazil 8 . The Turkish study was conducted in a tertiary care hospital specializing in COVID‐19 management 9 .…”
Section: Parameter First Wave Pre‐delta Period (April 2 2020 To Janua...mentioning
confidence: 99%
“…The objective of the study was to understand the impact of symptomatic COVID‐19 on pregnant and postpartum women in India and compare the results with the study reported from low‐resource settings in Malawi, Africa, 2 representing LICs. We also compared the case fatality rates (CFRs) from NH, India, with those from Brazil, 8 Turkey, 9 South Africa, 10 and Mexico, 11 representing LMICs. The data in the Malawian study was collected from 33 district and central hospitals throughout Malawi 2 .…”
Section: Parameter First Wave Pre‐delta Period (April 2 2020 To Janua...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women are not more susceptible to SARS-CoV-2 infection, but they may face a more serious COVID-19, because of their unique physiological and immunological status [1].…”
Section: Introductionmentioning
confidence: 99%